Towards Better Care for Preterm Infants in Bamako, Mali - Sylla, Mariam; Kassogue, Djibril; Traore, Isabelle; Diall, Hawa; Charpak, Nathalie; Dicko-Traore, Fatoumata; N'diaye, Maimouna; Doumbia, Djeneba; Kamissoko, Fatoumata; Sidibe, Toumani; M. Keita, Mamadou (Current Women's Health Reviews, 2011)
Objective: The objective of this study was to assess the feasibility, acceptability and outcome of Kangaroo Mother Care (KMC) on low birth weight (LBW) infants, including morbidity and mortality related to prematurity. Methods: A longitudinal study of preterm infants in KMC at the Gabriel Toure University Hospital (CHU), Bamako, Mali. Data collected in the KMC unit using hospital and ambulatory records. Data entered withEpiInfo and analyzed with SPSS12.0. Results: Mortality in preterm infants was very high (41.4%) before admission to the KMC unit. More than a third (30.7%) of the 480 surviving LBW infants during the study period were admitted to the KMC unit. The mean age of mothers was 25 years, with an average of three antenatal visits per mother. Deliveries had taken place mainly in community and district health centers. The mean gestational age at birth was 32.5 weeks for a mean birth weight of 1355 g. All babies and families admitted met the KMC eligibility criteria. The mean age at admission in the KMC unit was 9 days, with a mean weight of 1432 g, a mean height of 41 cm, and a mean head circumference of 29 cm. Somatic growth was satisfactory with a mean weight gain of 19 g per day during admission. The mean age of entry into the outpatient KMC program was 9.16 days (range: 2-32 days). The overall mortality of preterm infants admitted to the KMC program was 7.91%. Mortality among the preterm infants who remained in the neonatal unit was 51.1%. The KMC deaths occurred mostly between discharge from the KMC unit and 40 weeks of gestational age. The most common difficulties recorded after discharge were non-compliance with periodic visits, the occurrence of gastrointestinal, infectious or neurological complications, and failure to grow. Conclusions: The KMC program has been accepted by all mothers and families. Infants admitted to KMC showed a satisfactory growth. The overall mortality was lower among preterm infants in KMC unit compared to those cared in the neonatal unit.
Keywords: prematurity